Improving erythropoiesis stimulating agents responsiveness in haemodialysis with less iron: an observational study - Carrilho,Patricia (2015)
Background: Prevalent haemodialysis (HD) patients have functional iron deficiency. Iron supplementation increases erythropoietic stimulating agents (ESA) responsiveness, but concern exists about overload. ESA responsiveness index (ERI) is currently used to quantify resistance to these agents. Frequent administra- tion of a small dose of intravenous (i.v.) iron might improve erythropoiesis, but evidence is lacking. Methods: The impact of switching from a variable, intermittent dose of iron sucrose to a frequent (thrice-weekly) fixed dose of 10mg of iron sucrose was assessed in a sequential observational study comparing two periods of 4 months before and 6 months after, in 51 stable haemodialysis patients receiving maintenance iron and ESA (i.v. darbepoetin alfa). Results: Demographics: mean age 66.2 ± 14 years, dialysis vintage 55 ± 58 months, 21% Black, 43% male. Mean Hb levels (g/dL) during the baseline period (10.9 ± 0.7) did not differ from the study period (11.05 ± 0.6), p = 0.061. Iron sucrose dose per patient/month was 203mg (IQR 117-217) during baseline and 130mg during the study period (p < 0.001), and the median dose of ESA per patient per month decreased 22% from 90 μg to 70 μg (p < 0.001), improving ERI from 6.17 to 4.47 (p < 0.001). While ferritin levels did not differ, mean TSAT at the end was significantly higher than at baseline (29.38 ± 10.8 vs. 23.76 ± 8.48 %, respectively, p < 0.001), suggesting improved availability of iron for erythropoiesis. Mean total monthly cost (including both i.v. iron and ESA) decreased 25%. Conclusion: Administration of less but more frequent iron allowed achieving target Hb, improving ESA response and reducing global costs